모유영양아와 인공영양아의 1 ~ 3개월의 성장발육 상태 평가 - 한국 표준치와 NCHS Reference간의 비교 - ( Evaluation of Growth between Breast-Fed and Formula-Fed Korean Infants from 1 to 3 Postpartum Months - Compared with the Korean Standard and NCHS Reference ) - 최경숙; 구재옥 (대한지역사회영양학회지, 1998)
This study compares the growth performance(weight-for-age Z-score, height-for-age Z-score, weight-for-height Z-score) of one- to three- month-old Korean infants(n=232) with the Korean standard(1994) and NCHS reference(1983). The weight-for-age Z-scores(WAZ) by the Korean standard were -2∼1,5 for males and -3∼1 for females. The NCHS reference, WAZ results were -1∼2.5 and -2.5∼3.5 for males and females, respectively. The WAZ compared Korean standard showed no subjects with overnutrition. But 1.3% of the infants showed signs of malnutrition. Comparison with NCHS reference revealed that 0.4% of the infants were malnourished and 7.0% of the infants were overnourished. The WAZ of formula-fed infants were distributed higher than breast-fed infants, but that was not significant. The height-for-age Z-score(HAZ) by the Korean standard were -4.5%∼1.5% for males and -4∼1.5% for females. According to the NCHS reference, HAZ were -2.5%∼2.5% and -3∼3 for males and females, respectively. When the WAZ was compared with the Korean standard, there was no overnutrition but 16% of the infants showed signs of malnutrition. The NCHS reference, revealed that 6.9% of the infants were malnourished and 1.8% of the infants were ovemourished. The weight-for-height Z-scores(WHZ) by the Korean standard were -2∼5 for males and -2.5∼5 for females. The NCHS reference WAZ scores were -1∼4 and -1.5∼4.5 for males and females, respectively. When the WHZ was compared with the Korean standard, 2.2% of infants were malnourished and 19.5% were overnourished. There were no malnourished subjects according to the NCHS reference and 19.1% of the infants were overnourished. When the three Z-scores are considered together, 92.0% of the infants should a normal growth status, there was no malnutrition, and 8.0% of the infants were overnourished. The growth performance was evaluated differently according to the type of standards. Thus, it is necessary to set proper growth standards for infants, according to which classification of feeding methods is chosen. A longterm and careful assessment of infants's growth performances to develop any group of standards.